The mapping and identification of the geodiversity geossitios to create trails geoturistic in Valley Stream St Joseph, in Caetés-PE - Bernardo, Wilson dos Santos; Lima, Carlos Eduardo Santos de; Costa, Samuel Othon de Souza; Gomes, Daniel Dantas Moreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper presents a surve yand mapping of geological heritage in this area that corresponds to the drainage network of the San Jose Creek, located in the municipality of Caetés, wild Pernambuco from observation sands tudie son the expeditions. The methodology consists of a literature review and fieldtrips for data collection and quantification analysis of geossítios with the methodusing the table of values of gray was taken: intrinsic value, cultural didactic científico, and were used GPS’s for determine the loalização geossítios, and the definition of possible trails that provide geoturísticas the study, appreciation and preservation of his geodiversity.